Investigating chemoreception and behavioural responses of Tetranychus urticae (Trombidiformes: Tetranychidae) to organic acids, aldehydes and essential oil components - Gaudet, Kayla; Faraone, Nicoletta; Hillier, Neil Kirk (Frontiers in Agronomy, 2023)
The two-spotted spider mite, Tetranychus urticae Koch, is a globally distributed polyphagous agricultural pest that is resistant to a variety of synthetic chemical pesticides. Plant essential oils have been recognized as a novel natural source of pest control that have a reduced impact to the environment and human health relative to synthetic pesticides, and which may provide a viable alternative for managing this pest. The present study focuses on assessing the potential of mite semiochemicals and essential oil constitutes as repellents and miticides. We developed an innovative electrophysiological approach (electrotarsography) to record olfactory sensitivity of T. urticae. Additionally, a novel two-choice behavioural assay was designed to determine whether T. urticae is attracted or repelled by selected compounds. Using Gas Chromatography-linked Electrotarsal detection (GC-ETD), we determined that T. urticae can sense many terpenoids commonly found in plant essential oils, such as eucalyptol, thymol, and linalool. In addition, T. urticae responded to carboxylic acids and aldehydes, which are known to be detected by ionotropic receptors. In two-choice behavioural assays, T. urticae was repelled by various essential oil active ingredients, as well as carboxylic acids and aldehydes. The study provides much needed insight to identify behaviourally relevant chemical cues for the development of mite control strategies.